IDENTIFIKASI KEBERBAKATAN ANAK USIA DINI DAN EVALUASI DALAM CABANG OLAHRAGA BOLAVOLI - Danang Wicaksono (Jorpres (Jurnal Olahraga Prestasi), 2016)
Sport cultivator to achieve the maximum peak achievement needs science and technology. Science and technology are always developing and will give many innovations in systemic and methodic sport cultivator process.The first stage in doing sport cultivator to achieve the maximum peak achievement is should be started in talent scouting process. Talent scouting is really needed in the effort of looking for best talent in a sport branch. The need of biomotor component, body adapting somatotype is differ from one sport branch to another. The quality body program will influence the maximum exercise result. The success of an exercise can be seen by doing an evaluation. Evaluation is done by doing some tests and measurements. In this article, it will be showed a test and measurement form which can done for volleyball athlete. Keywords: talent and evaluation